Role of fibreoptic bronchoscopy in early diagnosis of inhalational burns in patients with facial burns - Nosheen Kanchwala; R Ram Mohan; Komal Tripathi; Shilpi Baranwal; Manoj Kumar Jha; Sameek Bhattacharya (Wolters Kluwer Medknow Publications, 2021)
Introduction: Inhalation burn is a major cause of mortality in burn patients. Early diagnosis of smoke inhalation injury (SII) is imperative in the management and prevention of burn injury. The gold standard modality for the diagnosis of SII is fiber-optic bronchoscopy (FOB). Materials and Methods: This prospective, observational study included thirty patients and was conducted from November 2016 to May 2018. Patients with thermal burns sustained < 72 h with facial burns, age group 18-60 years, were included in the study. Results: FOB was done in thirty patients. About 26.67% of patients had closed space injuries. Singeing of scalp hair/eyebrows was present in 46.67% of patients. Singeing of nasal vibrissae/mustache was present in 56.67% of patients. Eversion of eyelids and lips was present in 33.33% and 50% of patients, respectively. Hoarseness of voice, edema of tongue, and tachycardia were present in 16.67%, 50%, and 66.67% of cases, respectively. On auscultation, 26.67% patients had basal crepts. In the chest X-ray, 16.67% of patients had pulmonary edema. Forty percent of patients had arterial hypoxemia and acidosis at the time of arrival. About 56.67% of patients were proved bronchoscopically to have features of SII. Conclusions: FOB has significant value in evaluation, prediction of prognosis, and management of SII when performed within 72 h of burns.